Finite Element Analysis Of Reinforced Concrete Slabs Supported By Different Stiffness Of Beam - Chai, Khem Fei (2020)
Reinforced concrete slab is one of the most important structure members that provide spacious platform for occupants to carry out activities. In the precomputer era, the structural analysis and design of slab were limited and tend to be too conservative. Moreover, the important relationship between the slabs and the supporting beams was ignored for simplicity and due to insufficient study towards the field such as provided in clause 3.5 in design code BS8110. This study will be focusing on the effects of different beam stiffness on the slabs internal loading through modelling in Scia Engineer Software, a structural finite element software. After that, the resulting bending moment and shear force obtained from Scia Engineer of linear analysis will then be compared with the corresponding values obtained based on the bending moment coefficients and shear force coefficients provided in BS8110 (British Standard: Structural use of concrete). The results shows that slab supported by flexible beam will exercise flat slab behaviour. In the case of slab supported by stiff beam, it shows ordinary beam-slab behaviour. For stiff beam supported slab, when the long span to short span ratio is relatively low, it also shows two-way slab behaviour, as the span ratio increase to a certain extent, the slab will show one-way slab behaviour which the bending moment and shear force at long span is very minute as compared to those in short span. BS8110 only adequately estimated the internal loading (namely bending moment and shear force) for slab supported by stiff beam of small ly/lx ratio. The bending moment and shear force of slab supported by flexible beam are generally underestimate by BS8110 whereas for slab supported by stiff beam of large ly/lx ratio are overestimated by BS8110.